Analysis of bioactive compounds and chemical composition of Malaysian stingless bee propolis water extracts - Syed Salleh, Sharifah Nur Amalina; Mohd Hanapiah, Nur Ayuni; Wan Johari, Wan Lutfi; Ahmad, Hafandi; Osman, Nurul Huda (Elsevier, 2021)
Propolis is a resinous substance collected by stingless bees containing bioactive compounds which exert various biological properties. The present study focused on the evaluation of chemical profiles produced by three Indo-Malayan stingless bee propolis extracted using water. Fresh propolis was collected from the same area and ecosystem conditions in Selangor, Malaysia, namely Tetrigona apicalis, Tetrigona binghami, and Heterotrigona fimbriata. The bioactive compounds and chemical composition of propolis extracts were then analyzed using gas chromatography–mass spectrometry (GC–MS). Results showed that propolis from the three different stingless bee species consisted of major groups such as sugar (31.4%), carboxylic acid (17.1%), terpenoid (14.3%), sugar alcohol (11.4%), hydrocarbon (5.7%), aldehyde (5.7%) amino acid (2.9%) and other constituents (11.4%). Heterotrigona fimbriata displayed the highest amount for both total phenolics (13.21 mg/mL) and flavonoids (34.53 mg/mL) compared to other propolis extracts. There is also no significant difference detected between all samples since p ≤ 0.05. In conclusion, this study shows that Malaysian stingless bee propolis contain bioactive components that have great potential to be used for their therapeutic and medicinal benefits. However, more investigations and analysis of stingless bee propolis need to be carried out in order to enhance the understanding and applications of propolis in the future.